The “polyglandular crisis” behind recurrent hyponatremia: misdiagnosis of a case of autoimmune polyglandular syndrome type 2 and clinical lessons learned - Yan, Manli; Wu, Hai; Deng, Jingyun; Wang, Yiting; Huang, Haoyue; Wei, Hua (Frontiers in Immunology, 2026)
Autoimmune polyglandular syndrome (APS) is a group of clinical syndromes resulting from genetic dysfunction of the immune system, affecting multiple endocrine glands as well as non-endocrine organs. Herein, we report a case of APS type 2 (APS-2) in an adult female, characterized predominantly by emaciation, fatigue, palpitations, and notably, refractory hyponatremia. In the late stage of her illness, the patient developed psychiatric abnormalities and was repeatedly hospitalized and treated in neurological facilities; however, no significant abnormalities were detected on relevant examinations. She was subsequently transferred to Guangdong Provincial Hospital of Traditional Chinese Medicine, where a comprehensive endocrine evaluation eventually led to the diagnosis of APS-2. The case was marked by highly non-specific clinical manifestations, which resulted in multiple episodes of misdiagnosis and missed diagnosis throughout her course of treatment. Drawing on the detailed clinical course of this patient and a review of relevant literature, this article analyzes the clinical heterogeneity, diagnostic challenges, and reasons for misdiagnosis associated with APS-2. Furthermore, it highlights the importance of dynamic monitoring of multiple glandular functions, enhancing clinicians’ recognition of this syndrome, and multidisciplinary collaboration to improve patient outcomes and reduce delays caused by misdiagnosis.